Socio-Cultural Determinants of Contraceptive Use among Rural Women Aged 15-29 Years from Marriage to First Live Birth (Ibrahim Medical College Journal, 2009)
Contraceptive prevalence rate (CPR) is lower while the fertility is higher among rural married women aged 15-29 in Bangladesh. Thus, this comparative study attempted to identify the socioeconomic and cultural determinants of contraceptive use in different rural settings. In this primary data based cross sectional study, a semi-structured questionnaire was applied to women aged 15-29 years in two rural areas who had at least one live birth on/before 20 December, 2006. The study areas were identified by multi-stage random sampling technique. Results showed that CPR was slightly higher in Dariadaulat (43.4%) than that of Chardigoldi union (41.6%) while the mean duration of use was slightly higher in Chardigoldi compared to Dariadaulat (5.04 v. 4.59 mo). Regression model for Dariadaulat (38.7% with P